The influence of rainfall on the Verreaux's eagle and its prey species in the Matobo hills, Zimbabwe - Nkomo, Merlyn (Department of Biological Sciences, 2022)
Understanding how species respond to variations in weather patterns will be crucial to improve our predictions about how species will cope with climate change. The Verreaux's Eagle (Aquila verreauxii) and its primary prey species the Rock Hyrax (Procavia capensis) and Yellow-spotted Hyrax (Heterohyrax brucei) have been monitored by a long-term citizen science project in the Matobo Hills, Zimbabwe. A previous study associated rainfall patterns with the establishment, breeding density and productivity of Verreaux's Eagles. Fluctuations in hyrax populations have been attributed to fluctuations in rainfall and drought. However, these studies have been limited by the use of total annual rainfall instead of targeted rainfall periods of when biological outcomes are most sensitive to weather phenomena. This study explored critical climate sensitivity windows influencing the Verreaux's Eagle's reading performance and the abundance of its main prey species. We used observations of 109 nests over 37 years (1984-2019) and counts from 20 hyrax den sites for 13 years (1993-2005), together with remotely sensed rainfall data. The probability of attempting to breeding and the probability of producing a fledgling was negatively associated with rainfall. For breeding attempt, the rainfall during June and July, 11-10 months before laying was the most relevant, whereas, for productivity, the rainfall during December to March, nine-five months before fledging was the most relevant. However, the relationship between the rainfall signal and breeding productivity was not significant. Hyrax abundance had a negative quadratic relationship with mean rainfall against their respective climate windows, whereby the abundance of adult and sub-adult hyrax increased with rainfall during July–September but declined thereafter at greater rainfall levels. The abundance of hyrax did not have a significant relationship with the breeding outcomes of the Verreaux's Eagles. This study shows the complexity of the causal relationships between climate and biological outcomes and also the value of long-term data to understanding the impacts of variations in weather patterns to better understand predator-prey dynamics.